Hubungan pengetahuan ibu nifas dengan perawatan luka perinium di PMB Aan Dyah Tahun 2020/2021 - Novitasari, Rista; Rosita, Evi (Jurnal Kesehatan Samodra Ilmu (JKSI), 2022)
The cause of maternal death in Indonesia is still dominated by bleeding (32%) and hypertension in pregnancy (25%), followed by infection (5%), old partus (5%), and abortion (1%) in addition to obstetric causes, maternal mortality is also caused by other causes (non obstetric) of 32%. As a result of improper perineal care can result in perineal conditions affected by lokchea and moisture will greatly support the proliferation of bacteria that can cause infections in the perineum. The purpose of this study to determine the relationship of maternal knowledge with perineal wound at PMB Aan Dyah. This research use analytical method by using primary data and secondary data. The population in this study is the number of mothers in the last 3 months totaling 65 respondents in June - August 2017. Sampling technique is total sampling. The result of the research was obtained, good postpartum mother as many as 25 people (38,5%), bad woman with bad knowledge about 40 people (61,5%), postpartum who do perineal wound care 15 respondents (23,1%), and postpartum mothers who did not perform perineal wound care as much as 50 respondents (76.9%). In chi square test to see the correlation between knowledge of postpartum mother and perineal wound care, p-value value of0.000 (p <0,05) was obtained, meaning that there was a significant correlation between maternal knowledge with perineal wound care. It is suggested to health officer to give counseling about perineal wound care on postpartum so that postpartum mother can know the importance of perineum wound care benefit.